Bank Profitability in Indonesia During COVID-19 Outbreak: Profitabilitas Bank di Indonesia Selama Wabah COVID-19 - Khalifaturofi'ah, Sholikha Oktavi; Listyarti, Indra; Poerwanti, Ririn; Sihotang, Ellen Theresia (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the factors of conventional bank profitability during the COVID-19 outbreak in Indonesia, using data from 52 conventional banks from 2020 Q1 to 2021 Q4. Using a fixed-effects model, bank-specific and macroeconomic factors are examined. The findings show that liquidity and bank size have a beneficial impact on profitability, whereas efficiency has a considerable negative effect. Additionally, non-performing loans have a favorable link with profitability. Notably, macroeconomic indices such as interest rates have a substantial impact on bank profitability, while capital, exchange rates, inflation, and economic growth do not. The study emphasizes the necessity of improved liquidity management, efficient operations, and strategic interest rate management in maintaining bank profitability and resilience in the face of disruptive occurrences